Dynamic contrast-enhanced ultrasound for assessment of skeletal muscle microcirculation in peripheral arterial disease - Amarteifio, Erick; Weber, Marc-André; Wormsbecher, Stephanie; Demirel, Serdar; Krakowski-Roosen, Holger; Jöres, Andreas; Braun, Simone; Delorme, Stefan; Böckler, Dittmar; Kauczor, Hans-Ulrich; Krix, Martin (Investigative radiology, 2011)
Objective: This feasibility study was performed to assess whether dynamic contrast-enhanced ultrasound (CEUS) and transient arterial occlusion are able to detect alterations in the microvascular perfusion and arterial perfusion reserve in patients suffering from peripheral arterial disease (PAD) in comparison with healthy volunteers. Materials and Methods: Twenty patients with PAD, Rutherford classification grade I, category III (mean age, 64 years; mean height, 173 cm; mean weight, 81.8 kg), and 20 volunteers (mean age, 50 years; mean height, 174 cm; mean weight, 77.8 kg) participated in the study. Low-mechanical index CEUS (7 MHz; MI, 0.28) was performed to the dominant lower leg after start of a continuous automatic intravenous injection of 4.8 mL suspension with microbubbles containing sulfur hexafluoride (SonoVue) within 5 minutes. Perfusion of the calf muscle was monitored by CEUS before, during, and after release of arterial occlusion at the thigh level lasting for 60 seconds. Several parameters, especially the time to maximum enhancement after release of occlusion (tmax), the maximum enhancement after release of occlusion (maxenh), the total vascular response after release of occlusion (AUCpost), and the resulting slope (m2) to maximum enhancement were calculated. Results: After release of the occlusion, a significantly delayed increase of the CEUS signal to maxenh was observed in the patients with PAD (32 ± 17 seconds) compared with volunteers (17 ± 8 seconds, P = 0.0009). maxenh was 66.5 ± 36.6 (∼mL) in PAD versus 135.6 ± 75.1 (∼mL) in volunteers (P = 0.0016). AUCpost was 3016.5 ± 1825.8 (∼mL·s) in PAD versus 5906.4 ± 3173.1 (∼mL·s) in volunteers (P = 0.0013), and m2 was significantly lower in PAD (3.8 ± 5.2 vs. 14.8 ± 9.7 [∼mL/s], P = 0.0001). Conclusions: Microvascular perfusion deficits and reduced arterial perfusion reserve in patients with PAD are clearly detectable with dynamic CEUS after transient arterial occlusion.
Gesehen am 02.03.2022